A multi-responsive luminescent Co(ii) coordination polymer assembled from amide-functionalized organic units for effective pH and cation sensing. Issue 5 (17th January 2023) - Wang, Luyao; Sun, Xiao; Cheng, Jiawei; Lu, Jing; Tian, Haiquan; Li, Yunwu; Dou, Jianmin; Wang, Suna
Abstract : A multi-responsive Co-CP demonstrates turn-on ratiometric/turn-off fluorescence sensing activities. Abstract : By employing an amide-containing multicarboxylate ligand of N, N ′′-(3, 5-dicarboxylphenyl)benzene-1, 4-dicarboxamide (H4 L), a 3D (3, 4, 4, 6)-connected Co(ii ) coordination polymer, namely, [Co(L)0.5 (tttmb)(H2 O)] n (LCU-112, LCU = Liaocheng University, tttmb = 1, 3, 5-tris(1, 2, 4-triazol-1-ylmethyl)-2, 4, 6-trimethylbenzene) has been constructed through solvothermal synthesis. LCU-112 demonstrates a novel (3, 4, 4, 6)-connected {4 2 .6}2 {4 2 .8 3 .10}{4 2 .8 4 }{4 4 .6 2 .8 7 .10 2 } net. Fluorescence measurements reveal that LCU-112 could display a highly sensitive fluorescence response to different pH systems, especially in the pH range from 3.93 to 4.46. It may also be viewed as a recyclable on-off-on vapoluminescent sensor responding to typical acidic and alkaline gases HCl and Et3 N. Remarkably, it exhibits excellent turn-on/ratiometric fluorescence sensing ability toward Pb 2+ and Al 3+ with a detection limit as low as 0.075 and 0.759 μM, respectively. LCU-112 also has a good fluorescence recognition function on Tb 3+ with a detection limit of 0.046 μM. Specially, Pb 2+ and Al 3+ ions can be further distinguished in the presence of Tb 3+ . For practical application, luminescent test papers for the detection of the above ions in tap water samples were designed. Furthermore, visualization of the quenching effect on Fe 3+ could also be improved by replacing LCU-112 with the post-synthesized sample Tb 3+ @LCU-112 . As a result, this Co-based coordination polymer could be explored as a multifunctional fluorescent material for environmental monitoring.